Approaching physically active learning as a multi, inter, and transdisciplinary research field - Mandelid, Mathias Brekke (Frontiers in Sports and Active Living, 2023)
In broad terms, physically active learning is a phenomenon that combines health and educational disciplines to integrate physical activity and core educational goals. Despite a growing research interest within the physically active learning field, conceptual clarity on combining and synthesising research disciplines appears to be needed. This article thus explores knowledge production within the physically active learning research field. First, it outlines the origin of the research field. Secondly, the terms multi-, inter-, and transdisciplinary are applied to confront how knowledge is produced. Finally, the three approaches' theoretical and ethical implications are discussed. The article contributes to conceptual clarity within the field by proposing that physically active learning is inherently inter-and transdisciplinary because it embraces the complexity of integrating and synthesising knowledge from health and educational disciplines to address real-world problems. To conclude, awareness of physically active learning's practical and theoretical dimensions through the three approaches is central to evolving the field.